Constitutionalizing the Senate: A Modest Democratic Proposal - Colón-Ríos, Joel; Hutchinson, Allan (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
The Senate Reference did not provide an ideal situation for clarifying the nature and limits of the power of constitutional reform in Canada. The facts gave the Court no choice but to recognize the fundamental role that the Senate plays in the Canadian constitutional order, and therefore to place some of its main features outside the scope of section 44 of the Constitution Act, 1982, even if they ran contrary to basic democratic values. For example, in order to explain that the implementation of consultative elections would alter the constitution’s basic structure, the Court was forced to construe in a negative light the prospect of a democratically legitimate Senate. In this paper, rather than attack or defend bicameralism, we will argue in favour of attributing a democratically reconstituted Senate with the primary responsibility of reviewing the constitutionality of legislation (as opposed to acting as a chamber of “sober second thought” with respect to the policy decisions of the House of Commons). Such an approach, we suggest, would augment the overall democratic legitimacy of the constitutional order.